RETRACTED: Asthmatic Airway Vagal Hypertonia Involves Chloride Dyshomeostasis of Preganglionic Neurons in Rats - He, Ding; Chen, Hong; Zeng, Ming; Xia, Chunmei; Wang, Jin; Shen, Linlin; Zhu, Danian; Chen, Yonghua; Wang, Jijiang (Frontiers in Neuroscience, 2020)
Airway vagal hypertonia is closely related to the severity of asthma; however, the mechanisms of its genesis are unclear. This study aims to prove that asthmatic airway vagal hypertonia involves disrupted neuronal Cl- dyshomeostasis. The experimental airway allergy model was prepared with ovalbumin in male adult Sprague-Dawley rats. Plethysmography was used to evaluate airway vagal response to intracisternal injected -aminobutyric acid (GABA). Immunofluorescent staining and Western-blot assay were used to examine the expression of microglia-specific proteins, Na+-K+-2Cl- co-transporter 1 (NKCC1), K+-Cl- co-transporter 2 (KCC2) and brain-derived nerve growth factor (BDNF) in airway vagal centers. Pulmonary inflammatory changes were examined with hematoxylin and eosin staining of lung sections and ELISA assay of ovalbumin-specific IgE in bronchoalveolar lavage fluid. The results showed that histochemically, experimental airway allergy activated microglia, upregulated NKCC1, downregulated KCC2, and increased the content of BDNF in airway vagal centers. Functionally, experimental airway allergy augmented the excitatory airway vagal response to intracisternally injected GABA, which was attenuated by intracisternally pre-injected NKCC1 inhibitor bumetanide. All of the changes induced by experimental airway allergy were prevented or mitigated by chronic intracerebroventricular or intraperitoneal injection of minocycline, an inhibitor of microglia activation. These results demonstrate that experimental airway allergy augments the excitatory response of airway vagal centers to GABA, which might be the result of neuronal Cl- dyshomeostasis subsequent to microglia activation, increased BDNF release and altered expression of Cl- transporters. Cl- dyshomeostasis in airway vagal centers might contribute to the genesis of airway vagal hypertonia in asthma.